Microencapsulation of Riboflavin (Vitamine B2) using Alginate and Chitosan : Effect of Surfactant Span 80 upon Microcapsule Diameter - YC. Danarto; Rochmadi Rochmadi; Budhijanto Budhijanto (Equilibrium Journal of Chemical Engineering, 2018)
Riboflavin (vitamin B2) plays an important role in the growth and maintenance of human metabolism. Riboflavin is the highly sensitive and unstable to environmental influences such as light, reducing agents and pH. Riboflavin is protected by forming it into microcapsules with sodium alginate as a matrix and coated with chitosan reinforced with glutraldehid crosslinking. This study aims to study the process of microencapsulation of riboflavin with sodium alginate and chitosan and is emphasized to study the effect surfactant span 80 upon the size of the microcapsules formed. Based on microcapsule size and its distribution,  it  can  be  concluded  that  more  span  80  added  to  paraffin  oil  will  reduce  the  size  of microcapsule that is formed